Complementary and Alternative Medicine Usage and Its Determinant Factors Among Infertile Men in Iran - Fatemeh Ghaedi Heidari; Mahlagha Dehghan; Sima Mokhtarabadi (Tehran University of Medical Sciences, 2020)
Objective: This study aimed to assess the use of some Complementary and Alternative Medicine (CAM) techniques in infertile men. Materials and methods: This cross-sectional study was conducted on 102 infertile men referred to the only center of infertility in Kerman, Iran using convenience sampling. Data were collected using a two-part researcher-made questionnaire and analyzed using descriptive and analytical statistics (chi-square test and logistic regression) with SPSS 16. Results: According to the present study, 72.5% of subjects used at least one of the CAM methods in the past year. Among them 28.4% of the subjects have used one CAM technique, 13.7% have used two techniques, 8.8% have used three techniques, 9.8% have used four techniques, and 11.8% have used more than four techniques since the last year. None of the socio-demographic characteristics had significant association with being the user of complementary and alternative medicines. Conclusion: The results showed that almost three quarters of the infertile men used CAM indicating a high prevalence of CAM usage among them.